Outline of philosophy - "Russell, Bertrand" (New York, 2007)
Philosophy, Russell argues, is concerned with the universe as a whole. He reveals how the world in which we seem to live differs from reality and makes clear how scientific advance has transformed our concept of the world.
Keywords: Philosophy